The Enzymatic Conversion of Phylloquinone to Menaquinone-4. - Al Rajabi, Ala. (2017)
Abstract: All forms of vitamin K share the naphthoquinone ring, but differ in the side chain. The naphthoquinone ring is the active site for the enzyme cofactor activity of vitamin K. Mammals have the ability to convert dietary phylloquinone into MK-4 and store the latter in specific tissues. This suggests that MK-4 plays a role beyond that of an enzyme cofactor. Several functions unique to MK-4 have been proposed. Recently, UBIAD1 was identified as the enzyme catalyzing prenylation of menadione with geranylgeranyl side chain forming MK-4. However, the exact mechanism by which phylloquinone is converted to MK-4 and the tissue localization(s) for this conversion are not known. We hypothesized that the phylloquinone's phytyl side chain is removed and a preformed geranylgeranyl side chain is added to the resultant menadione to form MK-4. The overall goal of this thesis was to provide direct evidence that menadione is the intermediate in this conversion. Menadione detection would provide insight into the location and mechanism by which phylloquinone is converted to MK-4. A highly reproducible HPLC method was developed and validated to measure menadione in urine. Archived urine samples of participants in a human phylloquinone supplementation study were analyzed (n=367). Phylloquinone supplementation resulted in a significant increase in urinary menadione secretion (P<0.0001). These results lend support to the hypothesis that menadione is an intermediate in the conversion of phylloquinone to MK-4. Furthermore, changes in urinary menadione excretion were significantly correlated with changes in biomarkers of vitamin K status, including serum phylloquinone and percent serum undercarboxylated osteocalcin (P=0.0008 and 0.02, respectively). In a separate metabolic study of 42 healthy men and women, we used deuterium-labeled (-d) collard greens to confirm that urinary menadione-d (MW 173-174) was formed from phylloquinone-d. For an intake of 255 nmol phylloquinone-d, up to 14.9%± 10.0% (mean± SD) was recovered as menadione-d in urine. The urinary menadione extraction method developed as part of this thesis, was subsequently modified to extract menadione from different matrices including rat urine, serum, tissues, cells and cell culture media. New menadione detection methods were developed using both LC/MS and LC-APCI-MS/MS. Male Fischer 344 rats (8 months; n=15) were fed 1.6 mg of phylloquinone-d (MW 459-463) per kg diet for 0 (control), 1 and 7 days. Using LC/MS, phylloquinone-d and MK-4-d (MW 446-449) were detected in tissues after 1 day. MK-4-d carried the d-label on the naphthoquinone ring, but not on the side chain, confirming the need for side chain removal for its formation. Using LC/MS, unconjugated menadione-d (MW 173-174) was measured in urine. Using LC-MS/MS, unconjugated menadione-d was detected in serum of rats (n=4/5 at day 1; n= 3/5 at day 7). A Caco-2 cell culture model was used to study the role of the enterocytes in the conversion process. Neither MK-4 nor menadione was detected in cells treated with phylloquinone. However, when treated with menadione, MK-4 was formed. These data suggest that enterocytes are not the location for the phytyl side chain removal step of this conversion. In conclusion, menadione can be measured in both urine and serum. This is the first time unconjugated menadione has been detected in biological materials. We demonstrated that newly formed MK-4 is synthesized from the dietary phylloquinone by the means of replacing the phylloquinone's phytyl side chain with the geranylgeranyl side chain. This conversion does not appear to occur in the enterocytes. Menadione is produced from dietary phylloquinone. Our findings support that menadione is an intermediate in phylloquinone to MK-4 conversion. Future studies are required to determine the exact location and function of this conversion.; Thesis (Ph.D.)--Tufts University, 2011.; Submitted to the Dept. of Biochemical and Molecular Nutrition.; Advisor: Sarah Booth.; Committee: John Suttie, and Sang-Woon Choi.; Keywords: Nutrition, Biochemistry, and Molecular biology.